Ureteral stent tube and preparation method thereof
By covering nano -fiber membranes composed of polyethylene glycol and polyethylene ester on the ureteriopathy tube, and using a variety of biodegradable materials to prepare the stent tube ontophytic body, the existing ureteral stent tube The injury of the urinary epithelium and the risk of urethra blocking have achieved higher biocompatibility and safety.
Patent Information
- Application Number
- CN202411350569.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-26
AI Technical Summary
Existing ureteral stent tubes are prone to damage to the urothelial during implantation and degradation, and may lead to the risk of urethral obstruction.
The stent tube body is covered with a nanofiber membrane. The nanofiber membrane is composed of polyethylene glycol and polyglycolide. The stent tube body is composed of polyglycolide, polyglycolide, polylactide, polycaprolactone and poly(p-lactide). It is composed of dioxanone and other materials and is prepared through electrospinning and blended weaving technology.
Reduce the irritation and damage to the urinary tract, prevent the growing and adhesion of the urinary tract, delay the risk of congestion of the urethra, and improve the biocompatibility and safety of the bracket tube.
Smart Images

Figure CN119345484A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of medical devices, and more specifically, to a ureteral stent and a preparation method thereof. Background Art
[0002] Ureteral stents are medical devices used to treat diseases and problems related to the urinary tract system and are widely used in urological surgeries. The earliest history of ureteral stents may have begun in the 19th century, when they were used as an auxiliary tool in the treatment of some open surgeries, with the main purpose of draining urine and maintaining ureteral continuity.
[0003] With the continuous development of medical technology, ureteral stents have been greatly improved in design and materials. Especially in the 20th century, with the continuous development of plastic preparation technology, polyethylene and polyvinyl alcohol began to be used in the research of ureteral stents, which are harder and easier to place. The design of ureteral stents has also undergone continuous improvement and innovation. From the original straight tube stent to the stent with a distal ball, to the single J and double J tube design, they are all designed to better adapt to the patient's physiological structure and reduce the occurrence of stent displacement and irritation symptoms.
[0004] At present, when the stent tube body is placed in the ureter, it is placed through an invasive operation. Since the stent tube body is mostly made of hydrophobic polymers, it is easy to cause damage to the urothelium during implantation, and often requires surgical removal, causing secondary damage. Degradable ureteral stents are a strategy to solve secondary damage. However, during the process of degradation in the patient's urethra, if the degradable material is easy to adhere to the upper urethral tissue, it will make it difficult to remove the degraded fragments in time, increasing the risk of urethral obstruction. Summary of the invention
[0005] In order to solve the above problems, the present application provides a ureteral stent tube and a preparation method thereof.
[0006] The ureteral stent provided in this application adopts the following technical solution: A ureteral stent tube comprises a stent tube body and a nanofiber membrane, wherein the nanofiber membrane is wound on the outer surface of the stent tube body by electrostatic adsorption, the nanofiber membrane components include polyethylene glycol and polyglycolide, the components of the stent tube body include component A and component B, the component A includes one or more of polyglycolide, polyglycolide, and polylactide, and the component B includes one or more of polycaprolactone and polydioxanone.
[0007] By adopting the above technical solution, the nanofiber membrane material selects polyethylene glycol and polyglycolide, which are both degradable materials with good biocompatibility. In addition, the nano-scale monofilament diameter allows the nanofiber membrane to enter the urethra tube relatively smoothly, which can further reduce the stimulation and damage to the urothelial tissue. And because of the dense barrier effect of the nanofiber membrane, it can prevent the urothelial tissue from growing in and adhering to the urothelial tissue. Component A and component B of the stent tube body are selected from materials with good biodegradability. These materials can gradually degrade in the body to form smaller molecular fragments, and the degradation rates of the materials used in component A and component B and the nanofiber membrane are different, which makes the degradation time of the urethral tube stent relatively dispersed during use, and will not produce degradation products in a concentrated manner. It is easier to be metabolized and discharged by the body, reducing the risk of urethra blockage.
[0008] Optionally, the nanofiber membrane component also includes fucoidan-modified chitosan.
[0009] Optionally, the preparation method of the fucoidan-modified chitosan is: Mix the fucoidan powder and deionized water in a mass ratio of 1:(6-8), heat to 50-70°C and stir for 30-50 minutes, and filter the fucoidan solution using a 0.4-0.5 μm filter membrane to remove insoluble matter; Mix chitosan powder with a 1-3% dilute hydrochloric acid solution in a mass ratio of 1:(15-20), heat to 45-55°C and stir for 50-60 minutes, and filter the chitosan solution using a 0.4-0.5 μm filter membrane to remove insoluble matter; The pretreated fucoidan solution and chitosan solution were mixed in a mass ratio of 1:(1-3), and stirred at 50-60°C for 2-3h. During the reaction, the pH value of the solution was adjusted to about 4-6; After the reaction is completed, 1-2 times the mass of ethanol is added to the solution, and the solution is centrifuged at a speed of 4000-5000 rpm for 5-15 minutes. The precipitate is collected, and the precipitate is washed with deionized water for 2-4 times. The washed precipitate is vacuum dried at 40-50° C. for 18-24 hours to obtain fucoidan-modified chitosan.
[0010] By adopting the above technical solution, the hydrophilicity of fucoidan-modified chitosan is improved. After adding fucoidan-modified chitosan to the nanofiber membrane, it can play a certain lubricating role in contact with water molecules, thereby reducing the friction with the urothelial tissue and reducing the physical damage to the urothelial tissue during implantation. And as the stent tube degrades, the nanofiber membrane will gradually degrade, but its lubricating properties can still be maintained during the degradation process, thereby continuously reducing friction in the urethra, reducing damage and discomfort. Both fucoidan and chitosan have antibacterial properties. When fucoidan is combined with chitosan, the modified material formed further enhances the antibacterial effect. The introduction of antibacterial materials can significantly reduce the risk of complications caused by urinary bacterial infections.
[0011] Optionally, a lubricant is sprayed on the side of the nanofiber membrane facing away from the stent tube body, and the lubricant includes 40-60 parts of acetylated hyaluronic acid, 30-40 parts of deionized water, 5-10 parts of phospholipids and 5-15 parts of gum arabic in parts by weight.
[0012] By adopting the above technical solution, acetylated hyaluronic acid has good stability and lubrication properties. It can form a smooth protective layer on the surface of the nanofiber membrane, significantly reducing the friction between the stent tube and the urothelium, thereby reducing physical damage to the urothelium. Phospholipid molecules can form a stable double-layer membrane structure in an aqueous solution. This structure has excellent lubrication and friction reduction effects, which can further reduce the resistance during stent tube implantation. The addition of gum arabic can not only improve the adhesion of the lubricant to the surface of the nanofiber membrane, but also has antibacterial properties. The various components in the lubricant have good biocompatibility and can reduce the stimulation of the stent tube to the urothelial cells.
[0013] In a second aspect, the present application provides a method for preparing a ureteral stent tube, using the following technical solution: A method for preparing a ureteral stent tube comprises the following steps: 30-50 parts of polyethylene glycol and 20-30 parts of polyglycolide are mixed by weight and then electrospun to obtain a nanofiber membrane; component A and component B are extruded and spun respectively, with a spinning diameter of 0.2-0.02 mm, and the spun yarns obtained by component A and component B are blended and woven into a 90-140ppi tube at a mass ratio of 4:(1-2), and then heated to 110-120°C, the spun yarns obtained by component B are melted and combined with the spun yarns obtained by component A, and the stent tube body is obtained after cooling; The surface of the stent tube body is cleaned and polished, and the nanofiber membrane is wound around the outside of the stent tube body by electrostatic adsorption to obtain a ureteral stent tube. The prepared ureteral stent tube is cleaned and disinfected.
[0014] By adopting the above technical scheme, a dense nanofiber membrane is obtained by electrostatic spinning, which ensures the structural stability of the membrane and the softness of the fiber membrane, which is beneficial to reduce the foreign body sensation and prevent the ingrown epithelial tissue. Component A and component B are extruded and spun separately, and are woven into a tubular structure of 90-140ppi through blending. Subsequently, under the condition of heating to 110-120°C, the spinning of component B melts and combines with the spinning of component A, achieving a close combination of the two materials, giving the stent tube good toughness and structural strength, and preventing the urethral stent from deformation and damage during use. The nanofiber membrane is wound around the outside of the stent tube body through electrostatic adsorption, achieving a close combination of the nanofiber membrane and the stent tube body, and the prepared ureteral stent tube is cleaned and disinfected to ensure the cleanliness and sterility of the stent tube and reduce the risk of infection.
[0015] Optionally, after the ureteral stent is cleaned, a lubricant needs to be sprayed on the surface of the nanofiber membrane, and the spraying thickness is 0.1-0.3 mm.
[0016] By adopting the above technical solution, the lubricant sprayed on the surface of the nanofiber membrane can significantly enhance the lubrication performance of the stent tube. The addition of lubricant can form a smooth protective layer on the surface of the stent tube, reduce friction with the urothelial tissue, reduce discomfort during stent tube implantation, and reduce the risk of damage to the urethral mucosa. By precisely controlling the spraying thickness, the discomfort to the patient can be minimized while ensuring the lubrication effect.
[0017] Optionally, the polyethylene glycol, polyglycolide and fucoidan-modified chitosan are mixed and then electrospinned to prepare the nanofiber membrane.
[0018] Optionally, the braiding angle of the spun blend obtained by weaving component A and component B is 45-60°.
[0019] By adopting the above technical solution, the braiding angle between 45-60° can make the stent tube body have better strength and elasticity, ensuring that the ureteral stent tube maintains sufficient strength and elasticity while withstanding urine flow and changes in the body environment, thereby extending its service life.
[0020] In summary, this application has the following beneficial effects: 1. Since the present application adopts polyethylene glycol and polyglycolide as the material of the nanofiber membrane, not only the degradability and biocompatibility of the material are ensured, but also the nanometer-scale monofilament diameter enables the fiber membrane to smoothly enter the urethra tube, reducing the stimulation and damage to the urothelial tissue. At the same time, the dense barrier provided by the nanofiber membrane effectively prevents the growth and adhesion of epithelial tissue. Component A and component B of the stent tube body are also selected from materials with good biodegradability. These materials gradually degrade in the body, and the difference in degradation rate avoids the concentrated production of degradation products, which helps to reduce the risk of urethral obstruction and improves the safety and biocompatibility of the stent tube.
[0021] 2. In this application, it is preferred to add fucoidan-modified chitosan to the nanofiber membrane, which not only significantly improves its hydrophilicity and lubricity, but also effectively reduces the friction with the urothelial tissue and reduces the physical damage during implantation. At the same time, as the stent tube gradually degrades, the nanofiber membrane can also maintain its lubrication properties, continuously reduce the friction in the urethra, and reduce the patient's discomfort. In addition, the antibacterial properties of fucoidan and chitosan themselves are further enhanced after modification, significantly reducing the risk of urinary tract bacterial infection and the complications caused by it, providing a safer and more effective solution for the clinical application of ureteral stents.
[0022] 3. The method of the present application ensures the structural stability and softness of the nanofiber membrane by weaving a high-density nanofiber membrane, while helping to reduce the foreign body sensation and prevent epithelial tissue from growing in. The spinning of component A and component B is woven into a tubular structure of 90-140ppi by blending, and component B is melted and combined with component A under heating conditions, giving the stent tube excellent toughness and structural strength to avoid deformation and damage during use. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 is a flow chart of a method for preparing a ureteral stent tube of the present application; Figure 2 is a cross-sectional view of the ureteral stent tube of the present application; Figure 3 It is a schematic diagram of the appearance of the stent tube body of the ureteral stent tube of the present application; Figure 4 It is a schematic diagram of the appearance of the nanofiber membrane of the ureteral stent tube of the present application. DETAILED DESCRIPTION
[0024] The present application is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the experiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.
[0025] Preparation example of fucoidan-modified chitosan Preparation Example 1 Preparation method of fucoidan modified chitosan: Add 1 kg of fucoidan powder and 7 kg of deionized water into a clean container and stir to mix. Heat the container to 60°C and use a stirrer to stir for 40 minutes. After stirring, filter the fucoidan solution with a filter membrane with a pore size of 0.4-0.5 μm to remove insoluble matter. 1 kg of chitosan powder was added into 18 kg of 2% diluted hydrochloric acid solution, heated to 50°C and stirred for 60 min using a stirrer. After stirring, the chitosan solution was filtered using a 0.4-0.5 μm filter membrane to remove insoluble matter. Mix 5 kg of fucoidan solution with 5 kg of chitosan solution, heat to 55°C and keep warm, stir at 30 r / min for 2.5 h. During the reaction, detect the pH value of the reaction solution and use sodium hydroxide or dilute hydrochloric acid to adjust the pH value of the solution to maintain at 5. After the reaction is completed, 10 kg of ethanol is added to the reaction solution and stirred evenly. The solution is centrifuged at 4500 rpm for 10 minutes, the precipitate is collected, and the precipitate is washed 3 times with deionized water. The washed precipitate is transferred to a vacuum drying oven and vacuum dried at 40-50° C. for 20 hours to obtain fucoidan-modified chitosan.
[0026] Preparation Example 2 Preparation method of fucoidan-modified chitosan: The difference from Preparation Example 1 is that 5 kg of fucoidan solution is mixed with 10 kg of chitosan solution.
[0027] Preparation Example 3 Preparation method of fucoidan-modified chitosan: The difference from Preparation Example 1 is that 5 kg of fucoidan solution is mixed with 15 kg of chitosan solution.
[0028] Preparation Example 4 Preparation method of fucoidan-modified chitosan: The difference from Preparation Example 2 is that during the reaction, the pH value of the reaction solution is detected, and the pH value of the solution is adjusted to 7 using sodium hydroxide or dilute hydrochloric acid.
[0029] Preparation Example 5 Preparation method of fucoidan-modified chitosan: The difference from Preparation Example 2 is that during the reaction, the pH value of the reaction solution is detected, and the pH value of the solution is adjusted to 3 using sodium hydroxide or dilute hydrochloric acid. Example
[0030] Example 1 A method for preparing a ureteral stent tube: 4 kg of polyethylene glycol and 2 kg of polyglycolide were prepared as raw materials for nanofiber membranes. The polyethylene glycol solution was dissolved in 6 kg of ethanol, and the polyglycolide was dissolved in 4 kg of hexafluoroisopropanol. The two solutions were divided into conjugate nozzles and conjugate electrospinning was performed to obtain nanofiber membranes.
[0031] Prepare 4kg of polylactide as component A, and prepare 1.5kg of polycaprolactone as component B. Put component A and component B into spinning equipment respectively for extrusion spinning. The spinning diameter range is 0.1±0.05mm. The spun fibers obtained from component A and component B are blended and woven around the bracket tube mold. The braiding angle is 55°, and the fibers are woven into a tubular structure with an outer diameter of 1.2mm and a density of 120ppi. Put the woven tubular structure into a vacuum heating furnace, set the heating temperature to 120°C, and melt the spun fibers of component B. In the molten state, the spun fibers of component B are combined with the spun fibers of component A. The combined tubular structure is taken out of the heating furnace and naturally cooled to room temperature. After cooling, the spun fibers of component B are solidified and firmly combined with the spun fibers of component A to form the bracket tube body.
[0032] Clean the surface of the stent tube body to remove the bumps and burrs on the surface, and use a polishing machine to polish the stent tube body to make it smooth and flat. Clean the surface of the nanofiber membrane to ensure that there is no damage or impurities, and cut it according to the size of the stent tube body. Start the high-voltage generator to form an electrostatic field between the electrode wire and the stent tube body. Use the electrostatic adsorption force and control the winder to make the nanofiber membrane fit the outside of the stent tube body. Use a pressure roller to press the nanofiber membrane to ensure that it fits tightly with the stent tube body.
[0033] The ureteral stent tube with the nanofiber membrane wound on it is placed in a cleaning tank, cleaned with appropriate purified water and dried, and the cleaned ureteral stent tube is placed in an ultraviolet disinfection device for disinfection. After the disinfection is completed, the ureteral stent tube is taken out for packaging and storage.
[0034] Example 2 A method for preparing a ureteral stent tube: The method is different from Example 1 in that 4 kg of poly(lactide-glycolide) is prepared as component A.
[0035] Example 3 A method for preparing a ureteral stent tube: The difference from Example 1 is that 4 kg of polyglycolide is prepared as component A.
[0036] Example 4 A method for preparing a ureteral stent tube: The difference from Example 1 is that 2 kg of poly(lactide-glycol) and 2 kg of poly(lactide) are prepared as component A.
[0037] Example 5 A method for preparing a ureteral stent tube: The difference from Example 1 is that 2 kg of poly(lactide-glycolide) and 2 kg of poly(glycolide) are prepared as component A.
[0038] Example 6 A method for preparing a ureteral stent tube: The difference from Example 1 is that 2 kg of polyglycolide and 2 kg of polylactide are prepared as component A.
[0039] Example 7 A method for preparing a ureteral stent tube: The difference from Example 1 is that 1 kg of poly(lactide-glycolide), 1 kg of poly(glycolide) and 2 kg of poly(lactide) are prepared as component A.
[0040] Example 8 A method for preparing a ureteral stent tube: The method is different from Example 1 in that 1.5 kg of polydioxanone is prepared as component B.
[0041] Example 9 A method for preparing a ureteral stent tube: The difference from Example 1 is that 0.7 kg of polydioxanone and 0.8 kg of polycaprolactone are prepared as component B.
[0042] Example 10 A method for preparing a ureteral stent: The difference from Example 1 is that 4 kg of polyethylene glycol, 2 kg of polyglycolide, and 1 kg of fucoidan-modified chitosan are prepared as raw materials for nanofiber membranes, the polyethylene glycol solution is dissolved in 6 kg of ethanol, the polyglycolide is dissolved in 4 kg of hexafluoroisopropanol, and the fucoidan-modified chitosan is dissolved in dilute hydrochloric acid with a mass concentration of 1%, and the three solutions are divided into conjugate nozzles for conjugate electrospinning to obtain nanofiber membranes. The fucoidan-modified chitosan is prepared by Preparation Example 1.
[0043] Embodiment 11 A method for preparing a ureteral stent: The difference from Example 10 is that the fucoidan-modified chitosan is prepared by Preparation Example 2.
[0044] Embodiment 13 A method for preparing a ureteral stent: The difference from Example 10 is that the fucoidan-modified chitosan is prepared by Preparation Example 3.
[0045] Embodiment 14 A method for preparing a ureteral stent: The difference from Example 1 is that after the ureteral stent is cleaned, a lubricant needs to be sprayed on the surface of the nanofiber membrane. The spraying thickness is 0.2 mm, and the lubricant contains 50 g acetylated hyaluronic acid, 35 g deionized water, 8 g phospholipids and 10 g gum arabic.
[0046] Comparative Example Comparative Example 1 A method for preparing a ureteral stent: The difference from Example 10 is that the fucoidan-modified chitosan is prepared by Preparation Example 4.
[0047] Comparative Example 2 A method for preparing a ureteral stent: The difference from Example 10 is that the fucoidan-modified chitosan is prepared by Preparation Example 5.
[0048] Comparative Example 3 A method for preparing a ureteral stent tube: The difference from Example 1 is that 5.5 kg of polylactide is prepared, the polylactide is placed in a spinning device for extrusion spinning, the spinning diameter range is 0.1±0.05 mm, and the spun fibers obtained from the polylactide are blended and woven around a stent tube mold with a braiding angle of 55°, woven into a tubular structure with a density of 120 ppi to form a stent tube body.
[0049] Comparative Example 4 A method for preparing a ureteral stent tube: The difference from Example 1 is that 5.5 kg of polycaprolactone is prepared, the polycaprolactone is placed in a spinning device for extrusion spinning, the spinning diameter range is 0.1±0.05 mm, and the spun yarn obtained from the polycaprolactone is blended and woven around a stent tube mold with a braiding angle of 55°, woven into a tubular structure with a density of 120 ppi to form a stent tube body.
[0050] Comparative Example 5 A method for preparing a ureteral stent tube: the difference from Example 1 is that the braiding angle is 40°.
[0051] Performance testing Detection Methods The ureteral stents obtained in Example 1, Example 10, Example 13 and Comparative Examples 1-2 were tested using a COF-P01 inclined plane friction coefficient tester to calculate the surface friction coefficient.
[0052] The ureteral stents obtained in Examples 1-14 and Comparative Examples 1-5 were placed in a container simulating a urethral tube environment with a pH value between 5 and 7.0, filled with simulated urine components including water, electrolytes (sodium, potassium, chlorine, etc.), and organic matter (urea, creatinine, etc.), maintained at a constant temperature of 37°C, and the degradation time was recorded.
[0053] Table 1 Friction coefficient test Friction coefficient Example 1 0.11 Example 10 0.06 Embodiment 13 0.02 Comparative Example 1 0.08 Comparative Example 2 0.09 Table 2 Degradation time It can be seen from Example 10 and Comparative Examples 1-2 and Table 1 that the product obtained by the preparation method of fucoidan-modified chitosan in the present application scheme has a higher effect when applied to the nanofiber membrane, can achieve lower friction, and reduce the patient's discomfort.
[0054] Combining Example 1 and Comparative Examples 3-4 with Table 2, it can be seen that the blended weaving of the two components A\B in the present application can effectively achieve graded degradation of the stent tube, so that the degradation products will not be concentrated in the same time period to cause blockage and discomfort.
[0055] It can be seen from Example 1 and Comparative Example 5 and Table 2 that a braiding angle between 45-60° can make the stent tube body have better strength and elasticity, ensuring that the ureteral stent tube maintains sufficient strength and elasticity while withstanding urine flow and changes in the body environment, thereby extending its service life.
[0056] Combining Examples 1, 10, and 13 with Table 1, it can be seen that fucoidan-modified chitosan improves hydrophilicity, and fucoidan-modified chitosan added to the nanofiber membrane in contact with water molecules can play a certain lubricating role, thereby reducing friction with the urothelial tissue and reducing physical damage to the urothelial tissue during implantation. The addition of lubricants can form a smooth protective layer on the surface of the stent tube, reduce friction with the urothelial tissue, reduce discomfort during stent tube implantation, and reduce the risk of damage to the urethral mucosa.
[0057] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A ureteral stent, characterized in that: It includes a stent tube body and a nanofiber membrane, wherein the nanofiber membrane is wound on the outer surface of the stent tube body by electrostatic adsorption, the nanofiber membrane components include polyethylene glycol and polyglycolide, the components of the stent tube body include component A and component B, the component A includes one or more of polyglycolide, polyglycolide, and polylactide, and the component B includes one or more of polycaprolactone and polydioxanone.
2. A ureteral stent according to claim 1, characterized in that: The nanofiber membrane component also includes fucoidan-modified chitosan.
3. A ureteral stent according to claim 2, characterized in that: The preparation method of the fucoidan-modified chitosan: Mix the fucoidan powder and deionized water in a mass ratio of 1:(6-8), heat to 50-70°C and stir for 30-50 minutes, and filter the fucoidan solution using a 0.4-0.5 μm filter membrane to remove insoluble matter; Mix chitosan powder with a 1-3% dilute hydrochloric acid solution in a mass ratio of 1:(15-20), heat to 45-55°C and stir for 50-60 minutes, and filter the chitosan solution using a 0.4-0.5 μm filter membrane to remove insoluble matter; The pretreated fucoidan solution and chitosan solution were mixed in a mass ratio of 1:(1-3), and stirred at 50-60°C for 2-3h. During the reaction, the pH value of the solution was adjusted to about 4-6; After the reaction is completed, 1-2 times the mass of ethanol is added to the solution, and the solution is centrifuged at a speed of 4000-5000 rpm for 5-15 minutes. The precipitate is collected, and the precipitate is washed with deionized water for 2-4 times. The washed precipitate is vacuum dried at 40-50° C. for 18-24 hours to obtain fucoidan-modified chitosan.
4. The ureteral stent according to claim 1, characterized in that: A lubricant is also sprayed on the side of the nanofiber membrane away from the stent tube body. The lubricant includes 40-60 parts of acetylated hyaluronic acid, 30-40 parts of deionized water, 5-10 parts of phospholipids and 5-15 parts of gum arabic in parts by weight.
5. A method for preparing a ureteral stent according to any one of claims 1 to 4, characterized in that: The following steps are involved: 30-50 parts of polyethylene glycol and 20-30 parts of polyglycolide are mixed by weight and then electrospun to obtain a nanofiber membrane; component A and component B are extruded and spun respectively, with a spinning diameter of 0.2-0.02 mm, and the spun yarns obtained by component A and component B are blended and woven into a 90-140ppi tube at a mass ratio of 4:(1-2), and then heated to 110-120°C, the spun yarns obtained by component B are melted and combined with the spun yarns obtained by component A, and the stent tube body is obtained after cooling; The surface of the stent tube body is cleaned and polished, and the nanofiber membrane is wound around the outside of the stent tube body by electrostatic adsorption to obtain a ureteral stent tube. The prepared ureteral stent tube is cleaned and disinfected.
6. The method for preparing a ureteral stent according to claim 5, characterized in that: After the ureteral stent tube is cleaned, a lubricant needs to be sprayed on the surface of the nanofiber membrane, and the spraying thickness is 0.1-0.3 mm.
7. The method for preparing a ureteral stent according to claim 5, characterized in that: The nanofiber membrane is prepared by mixing 30-50 parts of polyethylene glycol, 20-30 parts of polyglycolide and 5-15 parts of fucoidan-modified chitosan in parts by weight and then using electrostatic spinning.
8. The method for preparing a ureteral stent according to claim 5, characterized in that: The braiding angle of the blended yarns obtained by spinning component A and component B is 45-60°.
Citation Information
Patent Citations
A biodegradable braided ureteral stent and its preparation method
CN102266594A
Medical biocolloid solution and preparation method thereof
CN104740691A
Fucoidin micro-nano material and preparation method thereof
CN110184680A
Tool holder for turret of CNC lathe
KR1020190078549A